Muscle and bone characteristics of a Chinese family with spinal muscular atrophy, lower extremity predominant 1 (SMALED1) caused by a novel missense DYNC1H1 mutation - Yazhao Mei; Yunyi Jiang; Zhenlin Zhang; Hao Zhang (BMC, 2023)
Abstract Background Spinal muscular atrophy, lower extremity predominant (SMALED) is a type of non-5q spinal muscular atrophy characterised by weakness and atrophy of lower limb muscles without sensory abnormalities. SMALED1 can be caused by dynein cytoplasmic 1 heavy chain 1 (DYNC1H1) gene variants. However, the phenotype and genotype of SMALED1 may overlap with those of other neuromuscular diseases, making it difficult to diagnose clinically. Additionally, bone metabolism and bone mineral density (BMD) in patients with SMALED1 have never been reported. Methods We investigated a Chinese family in which 5 individuals from 3 generations had lower limb muscle atrophy and foot deformities. Clinical manifestations and biochemical and radiographic indices were analysed, and mutational analysis was performed by whole-exome sequencing (WES) and Sanger sequencing. Results A novel mutation in exon 4 of the DYNC1H1 gene (c.587T > C, p.Leu196Ser) was identified in the proband and his affected mother by WES. Sanger sequencing confirmed that the proband and 3 affected family members were carriers of this mutation. As leucine is a hydrophobic amino acid and serine is hydrophilic, the hydrophobic interaction resulting from mutation of amino acid residue 196 could influence the stability of the DYNC1H1 protein. Leg muscle magnetic resonance imaging of the proband revealed severe atrophy and fatty infiltration, and electromyographic recordings showed chronic neurogenic impairment of the lower extremities. Bone metabolism markers and BMD of the proband were all within normal ranges. None of the 4 patients had experienced fragility fractures. Conclusion This study identified a novel DYNC1H1 mutation and expands the spectrum of phenotypes and genotypes of DYNC1H1-related disorders. This is the first report of bone metabolism and BMD in patients with SMALED1.